The Relative Fertility of an Isolated Coral Tree, Erythrina indica - Wesley, H. D.; Wesley, Shoba V. (Indian Forester, 1990)
Three of the four Coral trees in a row were cut down and removed to investigate the relative productivity of the lone tree. There were altogether 463 inflorescences With 1032 fruits containing 4756 seeds. Four seeded fruits Were more numerous than the fruits with less or more seeds. The occurrence of a fruit with eleven seeds is indicatory of the genetic potentiality of the species. The enhanced efficiency in seed production is attributed to the activity of the three-striped squirrels. The floral prolificity is deemed a compensatory pre-adaptation for the enormous loss that occurs.